2011
DOI: 10.1080/01635581.2011.523504
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Leucine Restriction on Akt/mTOR Signaling in Breast Cancer Cell Lines In Vitro and In Vivo

Abstract: The mammalian target of rapamycin (mTOR) is a central controller of cell growth and is currently being investigated as a potential target in breast cancer therapy. The essential amino acid leucine has been proposed to regulate mTOR signaling. The objective of this study was to determine whether leucine restriction would inhibit mTOR signaling in breast cancer cells. Leucine restriction did not decrease mTOR signaling in any of the eight breast cancer cell lines tested. In addition, in vivo administration of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 58 publications
(59 reference statements)
0
12
0
3
Order By: Relevance
“…PI3K activity culminates in the phosphorylation and activation of protein kinase B (PKB, also known as AKT) . Growth factors have little or no effect on mTOR‐C1 signaling in the absence of specific amino acids such as leucine or arginine . Several mechanistic controls of mTOR‐C1 activation have been suggested including GTPase activator complexes, vacuolar H + ‐ATPases, cytosolic enzymes (such leucyl‐tRNA synthase) and specific membrane receptors; all of which directly sense and link specific amino acid sufficiency to mTOR‐C1 activation .…”
Section: Regulation Of Cell Growth Survival and Proliferation By Argmentioning
confidence: 99%
“…PI3K activity culminates in the phosphorylation and activation of protein kinase B (PKB, also known as AKT) . Growth factors have little or no effect on mTOR‐C1 signaling in the absence of specific amino acids such as leucine or arginine . Several mechanistic controls of mTOR‐C1 activation have been suggested including GTPase activator complexes, vacuolar H + ‐ATPases, cytosolic enzymes (such leucyl‐tRNA synthase) and specific membrane receptors; all of which directly sense and link specific amino acid sufficiency to mTOR‐C1 activation .…”
Section: Regulation Of Cell Growth Survival and Proliferation By Argmentioning
confidence: 99%
“…Une déplétion en leucine a ainsi permis d'augmenter l'apoptose au sein de 4 lignées cellulaires de mélanomes [28]. Cependant, dans une autre expérimentation menée sur 8 lignées cancéreuses mammaires différentes, une telle déplétion n'a pas permis d'inhiber la voie mTOR [14]. Mêmes résultats in vivo puisqu'une alimentation déplétée en leucine augmente significativement l'apoptose des cellules tumorales de souris immunodéprimées porteuses de xenogreffes tumorales (mélanome) [28] mais reste sans effet sur la suractivation de la voie mTOR des cellules tumorales mammaires portées par des souris [14].…”
Section: Modulation Nutritionnelle De L'effet Warburgunclassified
“…Cependant, dans une autre expérimentation menée sur 8 lignées cancéreuses mammaires différentes, une telle déplétion n'a pas permis d'inhiber la voie mTOR [14]. Mêmes résultats in vivo puisqu'une alimentation déplétée en leucine augmente significativement l'apoptose des cellules tumorales de souris immunodéprimées porteuses de xenogreffes tumorales (mélanome) [28] mais reste sans effet sur la suractivation de la voie mTOR des cellules tumorales mammaires portées par des souris [14]. Par contre, dans ce dernier modèle, le régime déplété en leucine a induit une perte de poids importante chez les animaux, effet pouvant être particulièrement délétère en termes de taux de survie.…”
Section: Modulation Nutritionnelle De L'effet Warburgunclassified
See 1 more Smart Citation
“…The expression of mTOR signalling has been found abnormal in several cancers and represents poor prognosis . Targets inhibiting the expression of mTOR could inhibit the proliferation and induce the apoptosis of cancer cells in vitro . All these suggested that mTOR should be a new target in the therapy of thyroid cancer.…”
mentioning
confidence: 99%